Shariah competency of Islamic finance students / Muhammad Syukran Yang Amri - Yang Amri, Muhammad Syukran (2018)
Islamic finance has become as one of the fastest growing sectors of the global financial system. This industry's rapid growth, undoubtedly it creates a huge demand for new expertise. As Islamic financial industry continued to experience growth, there is a dire need in highly skilled and talented human capital workforce that can drive the future developments and innovations of the industry. The necessities for the Islamic financial industry to expand and develop its human capital resources, ranks as high in priority as resolution of certain of the technical market challenges that practitioner continue to address. Because of the dire need for shariah talent, this paper will investigate the shariah talent among graduating Islamic finance students where the questionnaires were distributes among them to obtain the information. A total of 112respondents were selected for the purpose of this study. Data collected was analysed using descriptive analysis and reliability test. In general, findings of this study show that Islamic finance students have the element of shariah talent. Overall, this study gives some information on the competency of Islamic finance students.